THE INFLUENCE OF LEADERSHIP EMPOWERMENT ON INDIVIDUAL CREATIVITY WITH PSYCHOLOGICAL EMPOWERMENT AND SELF-LEADERSHIP AS MEDIATORS IN MSMES - Putra, Razor Adha Lesmana; Siswanti , Yuni; Hikmah , Khoirul (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyse the effect of leadership empowerment on individual creativity at Roti Wonosari, with psychological empowerment and self-leadership as mediating variables. The background of this research focuses on the importance of creativity in facing the challenges of Industry 5.0, particularly among SMEs that often encounter barriers to innovation. The research method utilizes a quantitative approach with statistical data analysis using Smart PLS 4. The sample consists of employees from Roti Wonosari, with a purposive sampling technique resulting in 48 respondents drawn from internal HR data. The findings indicate a significant positive effect of leadership empowerment on employee creativity. Psychological empowerment and self-leadership are proven to act as mediators that strengthen this relationship. Data analysis shows that enhancing leadership empowerment directly impacts individual creativity while boosting employee confidence and initiative. The final conclusion of this study emphasizes that to improve creativity at Roti Wonosari, the company should focus on effective leadership empowerment and support psychological empowerment as well as the development of employee self-leadership. This is expected to create a more innovative and responsive work environment.